2000
DOI: 10.1038/sj.bmt.1702400
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated bone marrow transplantation in children: outcome and a comparison with sibling donor grafting

Abstract: The clinical course of 59 children, who underwent BMT during 1988-1998 with a matched unrelated donor (MUD), was compared with 59 case controls receiving a sibling donor marrow. Thirty-eight patients had haematological malignancies while 21 had a nonmalignant disorder. The cumulative incidence of acute GVHD grade II-IV was 28% for MUD recipients vs 11% (P = 0.014) for sibling recipients. Extensive chronic GVHD was rare in both groups. The 5-year probability of survival was 52% for MUD vs 77% for sibling recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
43
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 23 publications
3
43
1
1
Order By: Relevance
“…We observed that patients receiving the hyperfractionated dose of 12 Gy had a trend towards a higher probability of developing chronic GVHD, considered the clinical expression of GVL. 1,5,14 As previously reported in transplanted patients with acute lymphoblastic leukemia patients, 15 HF-TBI dose may increase the capacity of donor marrow to engraft, either because of improved immunosuppression or because of a reduced incidence of minor residual host hemopoiesis which may be associated with a reduced relapse rate. 19 Our preliminary suggestions seem to be in contrast to the results obtained from a series of 116 patients receiving allogeneic bone marrow transplants from siblings or unrelated donors and conditioned with three different fractionated TBI regimens up to the total doses respectively of 10 Gy, 12 and 13.5 Gy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We observed that patients receiving the hyperfractionated dose of 12 Gy had a trend towards a higher probability of developing chronic GVHD, considered the clinical expression of GVL. 1,5,14 As previously reported in transplanted patients with acute lymphoblastic leukemia patients, 15 HF-TBI dose may increase the capacity of donor marrow to engraft, either because of improved immunosuppression or because of a reduced incidence of minor residual host hemopoiesis which may be associated with a reduced relapse rate. 19 Our preliminary suggestions seem to be in contrast to the results obtained from a series of 116 patients receiving allogeneic bone marrow transplants from siblings or unrelated donors and conditioned with three different fractionated TBI regimens up to the total doses respectively of 10 Gy, 12 and 13.5 Gy.…”
Section: Discussionmentioning
confidence: 91%
“…3,4 However, compared with SIB-HSCT, transplant from unrelated donors is associated with a high incidence of graft-versus-host disease (GVHD), morbidity and mortality. [5][6] Total body irradiation (TBI) is included in the vast majority of conditioning regimens to be used in SIB and UD-BMT, although busulfan-based conditioning regimens have been extensively reported. 7 The aims of TBI are to destroy the host marrow to allow repopulation with donor marrow cells, to achieve immunosuppression in order to prevent graft rejection and to eradicate leukemia cell population.…”
mentioning
confidence: 99%
“…However, severe graft-versus-host disease (GVHD) increases morbidity and mortality for haematopoietic transplantation from alternative donors when compared to HLA-matched siblings. [1][2][3][4] Pre-graft serotherapy directed against lymphocytes has been demonstrated to reduce the risk of severe GVHD. [5][6][7] Different types of pre-graft serotherapy have been used including monoclonal antibodies such as OKT3, or Campath 1G anti-CD52, or rabbit or horse polyclonal antibodies directed against thymocytes or T lymphocytes.…”
mentioning
confidence: 99%
“…9 In a previous study, comparing the outcomes of MUD and sibling graft recipients, we found a significant difference in occurrence of relapse between children who did or did not develop chronic GVHD. 2 We decided to further investigate this issue in the entire group of children transplanted for acute leukaemias at our centre. The aim of the present study was thus to examine whether a GVL effect also is present in the paediatric setting and to relate it to the occurrence of GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The original concept of SCT was to enable complete eradication of malignant cells by a maximum dose of chemoradiotherapy, bypassing the otherwise dose-limiting bone marrow aplasia with a salvaging autologous or allogeneic graft. In addition, now a well-established belief in the immunotherapeuthic potential of the allogeneic graft has evolved, usually described as the graft-versus-leukaemia (GVL) effect.…”
Section: Discussionmentioning
confidence: 99%